TRANSFORMASI TUGAS E-LEARNING PAI: MENGGESER PARADIGMA OBJEK TEORITIS MENJADI SUBJEK NARATIF DALAM REFLEKSI KEBERAGAMAAN SISWA - Ulya Maysyaroh; Hamam Burhanuddin (STKIP Subang, 2026)
This study examines the transformation of e-learning task design in Islamic Religious Educatio from a theoretical object-oriented approach to a narrative subject-based reflective approach. The study is motivated by the tendency of current e-learning practices to replicate conventional assignments, limiting students’ engagement and inhibiting the internalization of religious values. The objective of this research is to conceptualize a reflective narrative-based e-learning task model that promotes deeper spiritual awareness among students. This study employs a qualitative approach using a library research method, analyzing relevant national and international scholarly literature on e-learning, student engagement, and reflective learning in religious education. The data were collected through documentation techniques and analyzed using content analysis to identify conceptual patterns and research gaps. The findings indicate that effective e-learning in PAI depends not on technological sophistication but on pedagogical transformation, particularly in designing tasks that encourage personal reflection and meaning-making. The study proposes a conceptual model consisting of stages including value stimulation, personal reflection, spiritual narrative construction, dialogic interaction, and reflective evaluation. This model positions students as active subjects who construct their own religious understanding through lived experiences. In conclusion, transforming e-learning task design into a reflective narrative framework enhances the meaningful internalization of Islamic values and supports the development of students’ spiritual identity in the digital era.